Null subjects in Englishes a comparison of British English and Asian Englishes - Schröter, Verena (Topics in English linguistics ;, 2019)
This book presents the first systematic quantitative study of null subjects not only in British English, but also in the contact varieties Indian, Hong Kong and Singapore English. Analysing informal spoken language, it addresses issues relevant for language contact and World Englishes, corpus linguistics and variationist sociolinguistics, linguistic typology and syntax.